Welding of metallic materials : methods, metallurgy, and performance - Khoshnaw, Fuad M. (Elsevier, 2023)
Welding of Metallic Materials: Methods, Metallurgy and Performance looks at technical welding methods used based on different principles and sources, such as heat, with or without pressure, electrical, plasma, laser and cold-based welding. The metallurgical aspects associated with the welding processes, specifically those associated with metallic alloys, are explained, alongside the advantages and welding features that are associated with specific welding processes. In addition, the performance of metallic weldments under specific conditions and environments such as offshore, oil industry, radiation and high-temperature services are discussed. This book will a vital resource for researchers, practicing engineers and undergraduate and graduate students in the field of materials science and engineering.